Application of Stiching Method in Vertebrae Radiography ExaminationLong Spine for Scoliosis Cases: Case Study at Waled Regional Hospital - Imamul Janna, Ahmad; Beni, Muhammad; Casidi, Casidi; Sinaga, Sunita (Jurnal Ilmu Kesehatan (JIKSAN), 2025)
Background: Scoliosis is a spinal bone deformity characterized by lateral curvature of the vertebral column to the right or left. Long spine vertebrae radiography is a diagnostic examination to detect scoliosis. Purpose: To describe the application of stitching method in long spine vertebrae radiography examination for scoliosis cases at Waled Public Hospital. Method: A descriptive qualitative study on 3 scoliosis patients who underwent long spine vertebrae radiography examination at Waled Public Hospital from June 2024. Data were collected through observation and interviews. Result: The radiography technique used anteroposterior and lateral projections. The stitching method combines radiography results into a single image so the entire vertebrae can be seen. The image was able to assess vertebrae anatomy for scoliosis diagnosis. Conclusion: Long spine vertebrae radiography examination using the stitching method can display the entire vertebrae in a single image, making it easier for radiologists to see and assess vertebrae anatomy for scoliosis diagnosis.